2006
DOI: 10.1073/pnas.0605355103
|View full text |Cite
|
Sign up to set email alerts
|

Protein complex formation by acetylcholinesterase and the neurotoxin fasciculin-2 appears to involve an induced-fit mechanism

Abstract: Specific, rapid association of protein complexes is essential for all forms of cellular existence. The initial association of two molecules in diffusion-controlled reactions is often influenced by the electrostatic potential. Yet, the detailed binding mechanisms of proteins highly depend on the particular system. A complete protein complex formation pathway has been delineated by using structural information sampled over the course of the transformation reaction. The pathway begins at an encounter complex that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…This suggestion is supported by molecular dynamics simulations of the SRL RNA, which show that the tetraloop has only limited flexibility on a 25-ns time scale (24). The apparent ''induced fit'' implicated here is reminiscent of the observations of a recent molecular dynamics study (25), in which binding to a protein partner was found to speed up the conformational transitions of another protein significantly.…”
Section: Resultssupporting
confidence: 67%
“…This suggestion is supported by molecular dynamics simulations of the SRL RNA, which show that the tetraloop has only limited flexibility on a 25-ns time scale (24). The apparent ''induced fit'' implicated here is reminiscent of the observations of a recent molecular dynamics study (25), in which binding to a protein partner was found to speed up the conformational transitions of another protein significantly.…”
Section: Resultssupporting
confidence: 67%
“…4a). Computer simulations have provided evidence for both conformational gating 44 and an IF mechanism 45 of binding to AChe. The ensemble representing the unbound state of FAS2 that was generated from the unbound crystal structure contained conformational variability in all three loops, but most noticeably in loop II (Fig.…”
Section: Energy Function and Discriminationmentioning
confidence: 98%
“…Deviations may in part be caused by approximations in our procedure (in particular, not including the Mn 2ϩ labels in the simulations). In addition, the underlying coarsegrained energy function ignores atomic detail (13,28), and the resulting small k B T-scale errors can significantly affect the relative populations.…”
Section: Pre Profiles From Simulation and Experimentmentioning
confidence: 99%
“…protein binding ͉ transient nonspecific encounter complexes ͉ paramagnetic relaxation enhancement ͉ bacterial phosphotransferase system E xperimental and theoretical studies have provided evidence that transient nonspecific encounter complexes play an important role in protein binding and function (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The formation of weakly bound nonspecific complexes, often dominated by long-range electrostatic interactions, enhances the on-rate of binding by increasing the interaction cross-section and reducing the conformational space to be searched on the path to the specific complex.…”
Section: Recent Paramagnetic Relaxation Enhancement (Pre) Studies On mentioning
confidence: 99%